Linear and nonlinear optical properties of erbium doped zinc borotellurite glass system - Abd Azis, Muhammad Noorazlan; Mohamed Kamari, Halimah; Ab. Aziz, Sidek (Elsevier, 2017)
A glass series of erbium doped zinc borotellurite glass system was prepared by using the melt-quenching method. The absorption spectra revealed several bands at visible range which correspond to the following transitions (from the ground state); 4G11/2 + 2H9/2 + 4F5/2 + 4F7/2 + 2H11/2 + 4S3/2 + 4F9/2 + 4I9/2 + 4I11/2. From the Judd–Ofelt analysis, it is found that the trend of Ω2 values is a non-linear variation along with erbium concentrations. Meanwhile, the value of Ω6 decreases as the erbium concentration increases. The photoluminescence analysis shows green emission which are attributed to the 4S3/2 level to the ground state at 4I15/2. Meanwhile, the upconversion analysis revealed several emission bands at 376 nm, 424 nm, 470 nm and 558 nm which correspond to 4G11/2 → 4I15/2, 4F3/2 → 4I15/2, 4F7/2 → 4I15/2 and 4S3/2 → 4I15/2 transitions respectively. The non-linear refractive index spectra show self-defocusing behavior and negative nonlinear refraction (ƞ2<0) under laser excitation at 532 nm of wavelength. The obtained values of nonlinear absorption and nonlinear susceptibility revealed nonlinear variations.